**Weegy:** (6z^2 - 4z + 1)(8 - 3z) = -18z^3 + 12z^2 - 3z + 48z^2 - 32z + 8 = -18z^3 + 60z^2 - 35z + 8

**User:** Simplify b(a + b) - a(a - b).

**Weegy:** b(a + b) - a(a - b) (ab + b^2) - (a^2 + ab) = -a^2 +2ab + b^2

**User:** Find the product.
(2p + 7)(3p - 9)

**Weegy:** (2p + 7)(3p - 9) = 6p^2 - 18p + 21p - 63 = 6p^2 + 3p - 63

**User:** Find the product.
-2x(x 2 - 3)

**User:** Find the quotient.
(35n 3 - 30n 2 + 25n) ÷ (-5n)

**Weegy:** (35n^3 - 30n^2 + 25n) / (-5n) = -7n^2 + 6n - 5

**User:** Find the product.
3y 2 z(2y 2 z + 4yz - y + z)

**Weegy:** 3y^2z(2y^2z + 4yz - y + z) = 3y^2z*2y^2z + 3y^2z*4yz - 3y^2z*y + 3y^2z*z = 6y^4z^2 + 12y^3z^2 - 3y^3z + 3y^2z^2

**User:** Find the product.
(6a + b)2

**Weegy:** (6a + b)^2 = 36a^2 + 6ab + 6ab + b^2 = 36a^2 + 12ab + b^2

**User:** Find the product.
(7q - 5)(7q + 5)

**Weegy:** (7q - 5)(7q + 5) = 49q^2 + 35q - 35q - 25 = 49q^2 - 25

**User:** Find the quotient.
y 9 ÷ y 3

(More)